Fetal Magnetic Resonance Imaging of Head and Neck Anomalies - Ho, Mai-Lan; Glastonbury, Christine M.; Glenn, Orit A. (Journal of Pediatric Neuroradiology, 2016)
Fetal head and neck (HN) anomalies represent complex diagnostic and management challenges, often requiring serial imaging and a multidisciplinary team approach. In this article, we will review the prenatal magnetic resonance imaging diagnosis of HN malformations, with ultrasound and postnatal imaging correlation. Key topics to be discussed include craniofacial abnormalities, posterior fossa malformations, neural tube defects, cervicofacial masses, and airway anomalies.
Keywords: fetal; prenatal; head and neck; magnetic resonance imaging